Genetic Response of Solanum lycopersicum L. (Tomato) to Phytophthora infestans and Aspergillus niger - Tavershima Moses Anakaa; Odunayo Joseph Olawuyi; Segun Gbolagade Jonathan (International Journal of Plant Biology)
There is limited information on the genetic response of tomato cultivars to pathogens. This study investigated the genetic mechanism of tomato that confers tolerance against Phytophthora infestans (Ph) and Aspergills niger (Asp) infection using different tomato accessions. Also, the study examined the effect of Ph and Asp infection on the morphology and the chromosome number of the infected tomatoes. Thirty tomato seed accessions were grown in a screen house, using a complete randomized design in triplicate, and evaluated for tolerance to both pathogens using a disease severity rating scale of 1 (highly tolerant) to 6 (highly susceptible), while chromosome assessment was performed using Carnoy’s protocol. Morphological data of 28 characteristics were collected using an IPGRI descriptor, while variance components, genetic advance (GA), and heritability were estimated for treated tomatoes and controls using the R statistical program. Accession NHT0254b, which was highly tolerant to Ph (1.00 ± 0.00) and Asp (1.33 ± 0.58), was diploid (2n = 2x = 24). The Ph-treated NHT0343a was moderately susceptible (3.67 ± 2.31), with 2n = 2x = 23, while NGB00711 was moderately susceptible (4.33 ± 1.16) with 2n = 2x = 22 after Asp treatment, indicating aneuploidy. In Ph treatment, cumulative fruit weight (CFW) had the highest environmental variance (1509.57), while number of seeds (NS) showed the highest genotypic variance (8.22). In Asp treatment, NS exhibited the highest genetic advance (2.97), while CFW had the highest phenotypic variance (754.91). Heritability estimates showed that fruit length (63.0%), the size of core (65.0%), and number of chambers (60.0%) were tolerant to Ph, while only fruit length (56.0%) was tolerant to Asp in terms of yield characteristics. Thus, tolerant accessions and traits are recommended for selection and genetic improvement.